2022
DOI: 10.1111/jmwh.13331
|View full text |Cite
|
Sign up to set email alerts
|

Salary and Workload of Midwives Across Birth Center Practice Types and State Regulatory Structures

Abstract: Introduction: Expansion of the midwifery-led birth center model of care is one pathway to improving maternal and newborn health. There are a variety of practice types among birth centers and a range of state regulatory structures of midwifery practice across the United States. This study investigated how those variations relate to pay and workload for midwives at birth centers.Methods: Data from the American Association of Birth Centers Practice Survey and the Bureau of Labor Statistics' report on occupational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…21 A secondary data analysis of 2 national surveys of midwives practicing in birth centers was published in 2022. 22 The analysis revealed that midwives working in birth centeronly practices report lower salaries when compared with midwives who work in a blended birth center or a hospital practice despite working a high number of hours. Of the 4 regions in the United States, midwives working in birth centeronly practices located in the Northeast had the highest salary (mean, $77,900).…”
Section: Literature Reviewmentioning
confidence: 98%
See 3 more Smart Citations
“…21 A secondary data analysis of 2 national surveys of midwives practicing in birth centers was published in 2022. 22 The analysis revealed that midwives working in birth centeronly practices report lower salaries when compared with midwives who work in a blended birth center or a hospital practice despite working a high number of hours. Of the 4 regions in the United States, midwives working in birth centeronly practices located in the Northeast had the highest salary (mean, $77,900).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Of the 4 regions in the United States, midwives working in birth centeronly practices located in the Northeast had the highest salary (mean, $77,900). 22 An evident gap in the literature is noted for individual state workforce surveys of midwives.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations